(untitled) (Proceedings of the International Conference on Hospitality and Tourism Management, 2022)
Kampung Kuin (Kuin Tourism Village), located in Banjarmasin City, South Kalimantan Province, Indonesia, became one of the tourist villages selected by the Ministry of Tourism to be included in the 2010 PNPM Mandiri Tourism Program. However, the results of the monitoring and evaluation report of Kuin Tourism Village were never found. They were not found on the Ministry of Tourism website because the public could access only the PNPM Mandiri Tourism program from 2013. Thus, it is not known precisely how the program will run, and its success in Kuin Tourism Village as one of the tourist villages included in the program. Furthermore, Kuin Tourism Village has started losing its magic over time and no longer become an attractive destination in Banjarmasin or South Kalimantan. Therefore, this study aims to determine the implications of Kuin Tourism Village as a tourist village and level of sustainability by conducting an assessment using Categories A & B of the ISTA Criteria and then formulating a management strategy with a SWOT analysis using the IFAS matrix. This research is mix method which correlation between qualitative and quantitative methods. Research where the data collection methods used were interviews, observation, documentation; and tabulating the data. The data collection results showed that Kuin Tourism Village received a sustainable predicate with a final score of 278 and was included in Quadrant I (growth) on the SWOT diagram (S-O Strategy). However, two problems were found which hindered the management. Therefore, a formulated 14-point strategy aims to overcome and put Kuin Tourism Village as a leading tourist area again, with a more sustainable direction. Finally, the surrounding community will benefit economically from tourism activities.